(untitled) (Baština, 2024)
Fairytales are crucial for children’s psychological, moral, social, emotional, and cognitive development. Preschool children encounter numerous problems and their solutions through fairytales. By listening to, reading, and watching fairytales, children build their views of the world, shape their moral values, and become familiar with positive behavior models. Fairytales point to ethical problems and teach children to differentiate between good and evil in an age-appropriate way. This paper discusses the influence of fairytales on the development of preschool children. The concept of a fairytale, its structure and characteristics are described. The paper lists the most common fairytale motifs and points out the therapeutic aspect of fairytales. The significance of telling fairytales to chronically ill hospitalized children is also emphasized, as well as their identification with the main characters and expressing their fairytale experience through play, dramatization, and drawings. By their length, dynamic plot, and the speed at which realistic and fantastic images interchange, fairytales improve the attention, imagination, communication, and creativity of preschool children.